The role of self-esteem, optimism, deliberative thinking and self-control in shaping the financial behavior and financial well-being of young adults - Hashmi, Fatima (2022)
Publisher Copyright: © 2021 Hashmi et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.